The effect of racquet swing weight on serve kinematics in elite adolescent female tennis players - Whiteside, D.; Elliott, B.; Lay, B.; Reid, M. (Journal of Science and Medicine in Sport, 2014)
Collision models for hitting implements denote how ball speed and swing weight increase proportionally when swing speed and impact location are held constant. The biomechanical effects of swing weight interventions are less understood. This study examined the effects of swing weight on serving arm mechanics, racquet kinematics, impact location and ball speed in the tennis serve.